Activités biologiques de trois variétés de cendres de noyaux de dattes (DEGLAT-NOUR / MECH DEGLA / HMIRA) - ABED, Ikram (My University, 2023)
Date cores are wastes from several date processing industries, they are discarded or partially incorporated into animal feed. Several researches have revealed their richness in various interesting biochemical and mineral substances. Our research focuses on the methanol extraction of three varieties of date nuclei Phoenix dactylifera L. the varieties are DEGLAT-NOR, MECH-DEGLA and HMIRA. Chemical analyses revealed a high concentration of phenolic compounds (31.60mg EAG/g extract) for the variety HMIRA, 28.77mg EAG/g extract for DEGLAT-NOR and 20.39mg EAG/g extract for MECH-DEGLA and flavonoids 20.841 mg EQC/g dry extract for variety HMIRA, 15.711 mg EQC/g dry extract for DEGLAT-NOR, 13.333 mg EQC/g dry extract for MECH-DEGLA and results indicating high antioxidant activity with an IC50 of 1.64 mg/ml for variety HMIRA, DEGLAT-NOR confirms an IC50 of 1.835 mg/ml and IC50 of 2.017 mg/ml for the MECH-DEGLA variety. Date stones of the variety HMIRA have a higher antioxidant power than the varieties DEGLET NOUR, MECH-DEGLA. Due to its richness in polyphenols and flavonoids exceeds that of the other two varieties Antimicrobial activity was determined on four bacterial strains (Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus sublilis, Escherichia coli), using the disc diffusion method. The results indicate that the methanol extract of date nuclei of three varieties has antibacterial activity at different concentrations.
Keywords: Phoenix dactylifera L; Polyphenols; Flavonoid; Antioxidant activity; Antimicrobial activity